RNA-binding Protein, GADD45-alpha, p27(Kip1), p53 and Genotoxic Stress Response in Relation to Chemoresistance in Cancer - Sheikh, M. Saeed (Mol Cell Pharmacol, 2015)
Genotoxic chemotherapeutics particularly cisplatin remain effective for clinical management of various malignancies including lung cancer. However, the development of chemoresistance leads to treatment failure. The mechanisms by which tumor cells acquire resistance to chemotherapy are multifaceted in nature and some remain to be fully elucidated. Recently, a potential role of RNA-binding protein hnRNPA0 in chemoresistance of p53-defective lung cancer cells was reported. Genotoxic (DNA damaging) chemotherapy was reported to activate hnRNPA0 which in turn post-transcriptionally regulated p27(Kip1) and Gadd45-alpha by stabilizing their mRNAs. Regulation of p27(Kip1) and Gadd45-alpha led to enforcement of G1/S and G2/M checkpoints thereby providing time for DNA repair and thus, resistance to chemotherapy. The identification of a signaling network involving the kinase MK2, hnRNPA0, p27(Kip1) and Gadd45-alpha that may predict response to chemotherapy is an interesting finding. Further studies are now needed to gain additional insights as to whether this network is restricted only to a subset of tumors or more broadly relevant across multiple tumor types.